Have-on-Mask and Maintain-Physical-Distance: Are they the Outcome of Lockdown-Laws in Corona-Virus Crisis Country-Wise? - Rahman, Akim M. (Journal of Economics and Behavioral Studies, 2021)
The COVID-19 pandemic is an infectious disease that was initially detected in December 2019 in Wuhan City, China. Since then, it has been spreading country-wise on mild to severe scales, where Bangladesh, like most countries, was not prepared to meet the challenges. Addressing the crisis, Bangladesh, like many countries, starting with the philosophy of the traditional approach. In the 1st-wave of COVID-19, the government implemented lockdown laws and enforced to have-on-mask and maintain-physical-distance. However, no government effort was seen ensuring modern-approach for convincing people, making people for their way understanding consequences & preventive-measures thus people can take own decision facing perceived-risk. In the proposed approach, under Consumer Choice Theory, an individual’s utility received from using face-mask and maintaining distance is equal to expected utility. Here outcome depends on an individual’s efforts and the quality of the product individual uses. Any changes to these may risk getting infected, which may defeat the individual in fights with COVID-19. Rather than investing efforts only within main cities, the government could have reached out to rural areas by having local administration engaged. It could have weakened today’s trends of catastrophes. The proposed approach could have been appealing to people for their actions in choices. It could ensure peoples’ roles in society on moral-responsibility grounds. However, today’s nation is witnessing the 2nd-wave and strict lockdown with provisions of arrest, penalties for violators. Since the number of death and infected people daily remained almost unchanged and since the mostly populated rural-area situation is not fully known, it is difficult to assess the effectiveness of government policies where the empirical study is warranted overcoming limitation. But people are now familiar with consequences and preventive measures in choices. This progression was not free-of-cost but with high-price-tag “so many lives”, which could have been curtailed if modern strategies were in place.